Development of Religion Materials Based on Synectic Approach to Junior High School Students - Alfauzan Amin; Alimni Alimni (Institut Agama Islam Negeri Bengkulu, 2019)
Abstract: Development of Religion Materials Based on Synectic Approach to Junior High School Students. Problems faced by teachers and students is the lack of teaching materials that can enhance students' understanding of competence. The understanding ability not only from low ability but also come to advance level. Especially the aspects of understanding the abstract of religious material at the first school level. Objectives: The aim of the study was to produce religious teaching materials based on a synectic approach that was valid, practical and effective. Method: The research methodology is research and development. This type of research produces products such as teaching materials. Teaching materials are expected to help students carry out learning activities easier. Finding: Based on the results of the study, religious teaching materials in the understanding of abstract concepts, for junior high school students, have been tested and declared valid, practical and effective to use.Conclusion: The Religion Material has been tested and valid for use in studentAbstrak: Pengembangan Materi Agama Berdasarkan Pendekatan Synectic pada Siswa SMP. Masalah yang dihadapi oleh guru dan siswa adalah kurangnya bahan ajar yang dapat meningkatkan pemahaman siswa tentang kompetensi. Kemampuan pemahaman tidak hanya dari kemampuan rendah tetapi juga datang ke tingkat lanjutan. Terutama aspek-aspek memahami abstrak materi agama di tingkat sekolah pertama. Tujuan: Tujuan dari penelitian ini adalah untuk menghasilkan bahan pengajaran agama berdasarkan pendekatan synectic yang valid, praktis dan efektif. Metode: Metodologi penelitian adalah penelitian dan pengembangan. Jenis penelitian ini menghasilkan produk seperti bahan ajar. Bahan ajar diharapkan dapat membantu siswa melakukan kegiatan belajar dengan lebih mudah. Temuan: Berdasarkan hasil penelitian, bahan ajar agama dalam pemahaman konsep abstrak, untuk siswa SMP, telah diuji dan dinyatakan valid, praktis dan efektif untuk digunakan. Kesimpulan: Bahan Agama telah diuji dan valid untuk gunakan pada siswa